KONSEPSI MANUSIA DALAM PANDANGAN MASYARAKAT JAWA (STUDI PEMIKIRAN KI AGENG SURYOMENTARAM) - Muawwalul Alamsyah; Sidiq Rahmadi (Aqidah-ta: Jurnal Ilmu Aqidah, 2022)
Humans are a variable that can be seen and interpreted in many ways. In the view of the Javanese people, especially in the thoughts of Ki Ageng Suryomentaram. Humans are seen as creatures that have stages of creation to become perfect humans, Ki Ageng Suryomentaram emphasizes the aspect of how one knows oneself. Ki Ageng Suryomentaram is one of the Javanese figures commonly referred to as organic intellectuals, namely someone who has thoughts or ideas whose thoughts are formed because of the surrounding culture, especially Javanese culture. This research is library research. The purpose of the research is to make a description, a systematic description and the relationship between the phenomena to be investigated. The results of this research, humans are created through several stages which include substance, karep, and the real me.